Soluble amyloid precursor protein 770 is a novel biomarker candidate for acute coronary syndrome. Issue 9 (9th September 2013) - Kitazume, Shinobu; Yoshihisa, Akiomi; Yamaki, Takayoshi; Oikawa, Masayoshi; Tachida, Yuriko; Ogawa, Kazuko; Imamaki, Rie; Takeishi, Yasuchika; Yamamoto, Naomasa; Taniguchi, Naoyuki; Pierce, Michael; Taniguchi, Naoyuki
<x xml:space="preserve">Abstract</x> Most Alzheimer disease patients show deposition of amyloid β (Aβ) peptide in blood vessels as well as the brain parenchyma. We previously found that vascular endothelial cells express amyloid β precursor protein (APP) 770, a different APP isoform from neuronal APP695, and that they produce amyloid β peptide. We analyzed the glycosylation of APP770 and found that O‐glycosylated sAPP770 is preferentially processed by proteases for Aβ production. Because the soluble APP cleavage product sAPP is considered to be a possible marker for Alzheimer disease diagnosis, sAPP, consisting of a mixture of these variants, has been widely measured. We hypothesized that measurement of the endothelial APP770 cleavage product in patients separately from that of neuronal APP695 would enable us to discriminate between endothelial and neurological dysfunctions. Our recent findings, showing that the level of plasma sAPP770 is significantly higher in patients with acute coronary syndrome, raise the possibility that sAPP770 could be an indicator of endothelial dysfunction. In this review, we first describe the expression, glycosylation, and processing of APP770, and then discuss sAPP770 as a novel biomarker candidate of acute coronary syndrome.